Effects of organizational culture on faculty members’ Job satisfaction - Soltanizadeh, Nargess; Sanaei, Naser (Archives of Advances in Biosciences, 2015)
Organizational culture of an organization is one of the fundamental staffs’ job satisfaction factors. This study aimed to determine the effects of organizational culture on faculty members’ job satisfaction using Hofstede’s model. In a descriptive applied study 61 faculty members of Shahid Beheshti university of Medical Sciences were randomly selected and studies in 2015. Hofstede’s model were used to job satisfaction and measuring dimensions of organizational culture (distribution of high power, ambiguity aversion, masculinity/femininity and individualism/collectivism) by modified Hofstede’s model in five spectrums of Likert scale. The study population consists of 61 faculty members, %66.7 percent was women and %74.4 was married. Mean and standard deviation of age was 42.3±9.7 years old. Most of people were opposed to the distribution of high power and masculinity and demanding ambiguity aversion and collectivism. The rate of individualism variable effect was little more than power distribution. There was significant difference in ambiguity aversion among faculty members (p<0.001). The rate of job satisfaction was high among faculty members (p<0.001). Faculty members’ job satisfaction was high. Hence it could be concluded that keeping distribution high power and patriarchy in organizational culture and ambiguity aversion are crucial factors for faculty members’ job satisfaction.